2019
DOI: 10.1021/acs.jnatprod.8b01037
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Biscembranoids and Assignment of Their Relative and Absolute Configurations: Data Set Modulation in the Density Functional Theory/Nuclear Magnetic Resonance Approach

Abstract: Five new biscembranoids, bistrochelides A–E (3–7), were isolated together with glaucumolides A (1) and B (2) from the soft coral Sarcophyton trocheliophorum. Their structures and absolute configurations were determined by spectroscopic methods, X-ray crystal diffraction, and DFT/NMR (density functional theory/nuclear magnetic resonance) and TDDFT/ECD (time-dependent density functional theory/electronic circular dichroism) calculations. A new approach is introduced to determine the relative configuration of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…Our previous investigation of secondary metabolites from the soft coral Sarcophyton glacum led to the discovery of two biscembranoid-type compounds, glaucumolide A ( 6 ) and glaucumolide B ( 7 ) [ 19 ]. The absolute configurations of 6 , 7 , and analogs have been confirmed in 2019 by Wen et al from the X-ray single crystal diffraction of the same compound 6 , isolated from the soft coral S. trocheliophorum [ 20 ]. Recently, with the development of molecular phylogenetic analysis technology, McFadden et al suggested that S. glacum contained more than seven genetically distinct clades which might be the reason for the continuous discovery of high chemical diversity of secondary metabolites of the soft coral S. glacum [ 38 ].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Our previous investigation of secondary metabolites from the soft coral Sarcophyton glacum led to the discovery of two biscembranoid-type compounds, glaucumolide A ( 6 ) and glaucumolide B ( 7 ) [ 19 ]. The absolute configurations of 6 , 7 , and analogs have been confirmed in 2019 by Wen et al from the X-ray single crystal diffraction of the same compound 6 , isolated from the soft coral S. trocheliophorum [ 20 ]. Recently, with the development of molecular phylogenetic analysis technology, McFadden et al suggested that S. glacum contained more than seven genetically distinct clades which might be the reason for the continuous discovery of high chemical diversity of secondary metabolites of the soft coral S. glacum [ 38 ].…”
Section: Resultsmentioning
confidence: 91%
“…Up to date, more than 60 biscembranoids biosynthesized via Diels–Alder reaction were isolated. Interestingly, these biscembranoids and their biosynthetic monocembranoid precursors are often found in Sarcophyton species [ 17 , 18 , 19 , 20 , 21 , 30 , 43 , 44 , 45 , 46 ]. The results of this study suggest that aquaculture of Sarcophyton species might produce structurally diversified bioactive compounds that could be beneficial for future drug development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our continuing search for bioactive molecules from marine invertebrates and the associated fungi [15][16][17], a strain of A. candidus was isolated from the internal tissues of the gorgonian coral Junceela fragillis, collected from the Xisha area of the South China Sea. Chemical investigation of the fermentation extract of this fungus resulted in the isolation of three new p-terphenyl derivatives and three new indole-diterpene alkaloids, together with eighteen known analogues.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] There is a growing recognition that microorganisms associated with marine invertebrate hosts might be the real producers of secondary metabolites. [9] During the ongoing quest for bioactive metabolites from the South China Sea invertebrates and associated microbes, [10][11][12] we paid specific attention to the discovery of terpenoid metabolites. From sponge Acanthella sp.…”
Section: Introductionmentioning
confidence: 99%